Extracellular Vesicles Arising from Apoptotic Cells in Tumors: Roles in Cancer Pathogenesis and Potential Clinical Applications - Lynch, Catherine; Panagopoulou, Maria; Gregory, Christopher D. (Frontiers in Immunology, 2017)
It is known that apoptotic cells can have diverse effects on the tumour microenvironment. Emerging evidence indicates that, despite its renowned role in tumour suppression, apoptosis may also promote oncogenic evolution or post-therapeutic relapse through multiple mechanisms. These include immunomodulatory, anti-inflammatory and trophic environmental responses to apoptosis which drive tumour progression. Our group has introduced the term “onco-regenerative niche” to describe a conceptual network of conserved cell death-driven tissue repair and regeneration mechanisms that are hijacked in cancer. We propose that, amongst the key elements of the onco-regenerative niche are extracellular vesicles (EVs), notably those derived from apoptotic tumour cells. EVs are membrane delimited sub-cellular particles, which contain multiple classes of bioactive molecules including markers of the cell from which they are derived. EVs are implicated in an increasing number of physiological and pathological contexts as mediators of local and systemic intercellular communication and detection of specific EVs may be useful in monitoring disease progression. Here we discuss the mechanisms by which EVs produced by apoptotic tumour cells – both constitutively and as a consequence of therapy – may mediate host responsiveness to cell death in cancer. We also consider how the monitoring of such EVs and their cargoes may in the future help to improve cancer diagnosis, staging and therapeutic efficacy.